2018
DOI: 10.1097/md.0000000000011568
|View full text |Cite
|
Sign up to set email alerts
|

Titanium elastic nailing versus locking compression plating in school-aged pediatric subtrochanteric femur fractures

Abstract: The treatment of children between 5 and 12 years of age suffering from subtrochanteric femoral fracture is challenging. The optimal choice of internal fixation for these patients is controversial. The purpose of this study is to compare the outcomes and complications of titanium elastic nail and open reduction with plate fixation of subtrochanteric femur fractures in school-aged children.A total of 67 children aged 5 to 12 years with subtrochanteric femur fractures treated with titanium elastic nails or open p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 17 publications
1
36
0
4
Order By: Relevance
“…Xu X et al 17 noted excellent outcome in 87% children while Wu QZ et al 18 reported excellent results in 76.9%, good in 15.3% and fair in 7.6% children. Some authors 19 are of the opinion that although plating is a rigid form of fixation it has minimal complications and produced excellent results in 67.8% and satisfactory in 32.1% children. In our study all the children achieved complete radiological union in 13.3±1.2 weeks (range 9.4 to 18 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Xu X et al 17 noted excellent outcome in 87% children while Wu QZ et al 18 reported excellent results in 76.9%, good in 15.3% and fair in 7.6% children. Some authors 19 are of the opinion that although plating is a rigid form of fixation it has minimal complications and produced excellent results in 67.8% and satisfactory in 32.1% children. In our study all the children achieved complete radiological union in 13.3±1.2 weeks (range 9.4 to 18 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Such results seem to be supported by some clinical evidence [14]. However, when the fracture is situated at proximal metaphysis the use of FINs is controversial [15,16,17].…”
Section: Introductionmentioning
confidence: 83%
“…Assim, Pombo e Shilt ( 2006) definiram fratura subtrocantérica como aquela localizada até o limite de 10% do comprimento total do fêmur, distalmente ao trocanter menor (POMBO; . O método em evidência, também usado por outros autores (XU et al, 2018;LI et al, 2013), foi adotado no presente estudo.…”
Section: Métodos Dos Elementos Finitos (Mef)unclassified
See 2 more Smart Citations